2000
DOI: 10.1063/1.1305324
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of liquid water in a magnetic field

Abstract: A Monte Carlo simulation of liquid water was carried out in order to study the influence of an external magnetic field on the internal energy and heat capacity of pure water. Analysis of the structure of water was made by calculating the radial distribution function of water molecules. A multipeak function of the magnetic effect versus magnetic flux density was found. A significant change in the internal energy and heat capacity occurred at a magnetic flux density of about 0.2 T. In particular, when the magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0
17

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(70 citation statements)
references
References 8 publications
0
53
0
17
Order By: Relevance
“…Former studies revealed that specific properties of water such as surface tension force and viscosity, optical property (changes in optical feature of water including infrared, Raman, visible, ultraviolet lights and X-ray spectra), electromagnetic property (refractive index, dielectric constant and electrical conductivity), thermodynamic property (enthalpy of vaporization), dynamic property (self-diffusion coefficient) and molecular structure of water (hydrogen bond structure) change upon the application of MFs [16,17,[22][23][24][25][26][27][28][29][30].…”
Section: Freezing Assisted By Magnetic Field (Fa-mf)mentioning
confidence: 99%
See 2 more Smart Citations
“…Former studies revealed that specific properties of water such as surface tension force and viscosity, optical property (changes in optical feature of water including infrared, Raman, visible, ultraviolet lights and X-ray spectra), electromagnetic property (refractive index, dielectric constant and electrical conductivity), thermodynamic property (enthalpy of vaporization), dynamic property (self-diffusion coefficient) and molecular structure of water (hydrogen bond structure) change upon the application of MFs [16,17,[22][23][24][25][26][27][28][29][30].…”
Section: Freezing Assisted By Magnetic Field (Fa-mf)mentioning
confidence: 99%
“…For instance, vaporization enthalpy of non-magnetized water was 50.86 ± 0.46 kJ mol −1 and its value increased to 68.86 ± 0.49 kJ mol −1 on exposure to MF with strength 45-65 mT for 3 h [23]. Simulation techniques, such as Monte Carlo (MC) and Molecular Dynamics (MD) simulation techniques have been used to examine the changes induced at a molecular level in liquid water by the application of MFs [23,26,27]. The observations by these groups were dissimilar.…”
Section: Freezing Assisted By Magnetic Field (Fa-mf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Comparatively, small-sized magnetic-treated water clusters strongly facilitate water permeability and the downward movement of salt ions [9,12]. As a result, soil salt ions, such as Cl -, Na + and HCO 3-, are significantly leached from the cultivation layer by magnetic-water irrigation [8].…”
mentioning
confidence: 99%
“…As water molecules (polymers) passing through a given intensity of a magnetic field, the large aggregate water cluster becomes into smaller particles, making both water and nutrients more accessible to plants [9][10][11].…”
Section: Introduction mentioning
confidence: 99%